2019
DOI: 10.1371/journal.pntd.0007856
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional infiltration versus parenteral use of meglumine antimoniate for treatment of cutaneous leishmaniasis: A cost-effectiveness analysis

Abstract: Cutaneous leishmaniasis (LC) is a complex and variable disease in terms of epidemiology, aetiology, pathology and clinical characteristics. The mainstay of treatment is still pentavalent antimony (Sbv) compounds administered systemically, despite their recognized toxicity. The advantages of antimony intralesional (IL) infiltration are the use of lower doses of Sbv and, therefore, less toxic effects. The objective of this study was to estimate the cost-effectiveness ratio of intralesional meglumine antimoniate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Regarding CL, two of the main findings are the confirmation of cost effectiveness of liposomal amphotericin B for hospitalized patients with mucocutaneous leishmaniasis and of the meglumine antimoniate intralesional approach, both in the context of the Brazilian National Health System. As a direct implication, these results should support the acquisition of liposomal amphotericin B for mucocutaneous leishmaniasis 16 and the implementation of an intralesional approach with meglumine antimoniate, as has already been done, for patients with localized CL in Brazil 17 .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Regarding CL, two of the main findings are the confirmation of cost effectiveness of liposomal amphotericin B for hospitalized patients with mucocutaneous leishmaniasis and of the meglumine antimoniate intralesional approach, both in the context of the Brazilian National Health System. As a direct implication, these results should support the acquisition of liposomal amphotericin B for mucocutaneous leishmaniasis 16 and the implementation of an intralesional approach with meglumine antimoniate, as has already been done, for patients with localized CL in Brazil 17 .…”
Section: Discussionsupporting
confidence: 54%
“…Brito et al 17 estimated the cost effectiveness of meglumine antimoniate intralesional infiltration (IL) compared to endovenous (IV) meglumine antimoniate therapy for the treatment of CL; the strategies had a total cost per patient cured of US$330.81 (IL) and US$494.16 (IV), respectively. The ICER showed that the intralesional meglumine antimoniate approach could result in savings of US$864.37 for each additional patient cured, confirming that the IL meglumine antimoniate strategy is cost effective in the context of the Brazilian public health scenario.…”
Section: Economic Analysis Of Treatmentmentioning
confidence: 99%
“…The ICER of US$495.32 per additional PQ-associated hospitalization avoided is less than 8% of one Brazilian GDP per capita (US$6,822). Although there is no explicit value to the cost-effectiveness threshold for a very efficient intervention in Brazil [ 24 ], CEAs conducted in the Brazilian context of neglected diseases have adopted interventions with ICERs up to one Brazilian GDP per capita for each additional unit of the health effect, including: hospitalization averted [ 19 ], days of hospitalisation avoided [ 25 ], case averted [ 26 ], and cure [ 27 ]. These outcomes are natural units that are intuitively understood in the health care field, facilitating decision making [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can be parental through amphotericin B deoxycholate, lipid formulations of amphotericin B, pentavalent antimonial compounds and pentamidine; oral options include miltefosine and the ‘azole’ antifungal compounds 4 . Nevertheless, based on the clinician’s experience, IL antimonials were preferred, knowing it has fewer side effects (and reduced costs) compared to systemic administration of anti‐leishmania drugs 9 . Alternative local therapies, such as cryotherapy or surgery, have a significant higher risk of anaesthetic scarring 9 or were excluded based on the difficult location of the lesion (thermotherapy) 10…”
Section: Report Of a Casementioning
confidence: 99%
“…Nevertheless, based on the clinician’s experience, IL antimonials were preferred, knowing it has fewer side effects (and reduced costs) compared to systemic administration of anti‐leishmania drugs 9 . Alternative local therapies, such as cryotherapy or surgery, have a significant higher risk of anaesthetic scarring 9 or were excluded based on the difficult location of the lesion (thermotherapy) 10…”
Section: Report Of a Casementioning
confidence: 99%